Helminth parasites of four species of strigiform birds from Central and Northeastern Argentina - Drago, Fabiana Beatriz (2015)
The helminthofauna of eight specimens of four species of strigiform birds from Central and Northeastern Argentina was studied. From all the specimens studied, the 75 % were positive for helminths. Seven taxa, that were previously known, are briefly described, and seven new host-parasite associations are reported: the strigeid digeneans Australapatemon magnacetabulum, and Strigea falconis brasiliana, and the acuariid nematode Synhimantus (Synhimantus) cf. laticeps (Acuaridae) associated with Asio clamator; the diplostomid digenea Neodiplostomum travassosi and the centrorhynchid acanthocephalan Centrorhynchus sp. parasitizing Athene cunicularia; the strigeid digenean Strigea magniova associated with Tyto alba; and the seuratid nematode Skrjabinura sp. parasitizing Megascops choliba. The host-parasite relationships are discussed through the analysis of host-specificity, diet of birds and life cycle of helminths. The richness of helminth taxa of strigiforms studied was moderate (1-3 species by host) and the infection intensity very low (1-3). Five taxa, out of seven, are considered “bird generalist” and the remaining two, “raptor generalist”.